Panaghanap: vehicle crash reporting assistant using microcontroller and piezoelectric sensor. - Ariega, Reginald A. Chua, Ruzzle Darwin D. Fernandez, Clark Aurve P. Guray, Georgeson Yssrael U. Lamagna, Aaron. 4 0 16; 5
u
Undergraduate Thesis : (Bachelor of Science in Computer engineering) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2